Gaming in the classroom and Gamification - Fuzaylova Nargiza Abdusamatovna (International Scientific and Current Research Conferences, 2023)
In this article, the use of gaming in educational settings has drawn attention recently as a potentially effective strategy for improving learning outcomes. This article investigates the possible advantages of employing games as teaching aids in the classroom.